Agrarian change and the changing relationships between toil and soil in Maragoli, Western Kenya (1900-1994) - Crowley, E.L.; Carter, Simon E. (Springer, 2000)
Theories of agrarian change in Africa normally treat agricultural intensification as a linear unidirectional process that gradually engulfs entire agrarian systems as human population increases. Focusing on soil management practices, this paper disputes the alleged uniformity of intensification and argues that periodic, contrary processes may occur simultaneously. Written and oral historical data, and survey data describing current farmers' practices and perceptions of change in densely settled Maragoli, western Kenya, are used to support this argument. Farmers' soil fertility management practices have changed in response to migration, social differentiation, and economic change, and the interplay between changing social and ecological conditions. Despite rapid population growth, Luhya farmers manage their soils both more and less intensively in response to this interplay and create a heterogeneous pattern of management in space and time. The implications of this variability for contemporary applied agricultural research in the region are assessed.